Buffering volatility: Storage investments and technology-specific renewable energy support - Jan Abrell; Sebastian Rausch; Clemens Streitberger (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
Mitigating climate change will require integrating large amounts of highly intermittent renewable energy (RE) sources in future electricity markets. Considerable uncertainties exist about the cost and availability of future large-scale storage to alleviate the potential mismatch between demand and supply. This paper examines the suitability of regulatory (public policy) mechanisms for coping with the volatility induced by intermittent RE sources, using a numerical equilibrium model of a future wholesale electricity market. We find that the optimal RE subsidies are technology-specific reflecting the heterogeneous value for system integration. Differentiated RE subsidies reduce the curtailment of excess production, thereby preventing costly investments in energy storage. Using a simple cost-benefit framework, we show that a "smart" design of RE support policies significantly reduces the level of optimal storage. We further find that the marginal benefits of storage rapidly decrease for short-term (intra-day) storage and are small for long-term (seasonal) storage independent of the storage level. This suggests that storage is not likely to be the limiting factor for decarbonizing the electricity sector.
Keywords: C63; Q42; Q48; Q54; 330; Renewable Energy; Electricity; Volatility; Intermittency; Storage; Technology-specific Regulation; Subsidies; Energy Policy; Climate Policy